Prediction of depth averaged velocity and boundary shear distribution of a compound channel based on the mixing layer theory. (August 2016) - Devi, K.; Khatua, K.K.
Abstract: The complexity of transfer of momentum between the main channel and flood plain in a compound channel can be tackled through the analytical solution of Shiono and Knight Method. Solution of this approach counts on the calibration of three indispensable parameters i.e., secondary currents, eddy viscosity coefficient and bottom friction. Due to uniqueness of these parameters, the boundary friction factor changes unevenly throughout the lateral direction especially at the shear layer region. In this paper, the analytical solution eventuating in the Shiono Knight Method is solved considering a new panel of shear layer width at the junction. Reliable experimental measurements are employed for quantification of shear layer width and to procure the new calibrating coefficients for secondary flow and friction factor for the proposed panels. The model is found to provide satisfactory results when applied to experimental, FCF channels and natural river data sets. Highlights: The coefficient i.e., friction factor used in solution of SKM has been modelled. An equation for secondary flow parameter ( k) has also been developed. An expression for computing the mixing length in shear layer region is derived. The models are validated against FCF data and field data sets.